Aerobic Exercise versus Electronic Cigarette in Vascular Aging Process: First Histological Insight - Vito A. Damay; null Setiawan; Ronny Lesmana; Muhammad Rizki Akbar; Antonia Anna Lukito; Vita M. Tarawan; Januar W. Martha; J. Nugroho; Sony Sugiharto (International Journal of Vascular Medicine)
Smoking is related to vascular aging. However, the hazardous effect of e-cigarette is often debatable, with limited studies available. In contrast, moderate-intensity aerobic exercise is well known to decrease aortic stiffness. We provide novel research to determine the effect of e-cigarette and aerobic moderate-intensity exercise on the aortic structure of Wistar rats. A total of 26 male Wistar rats (Rattus norvegicus) 8 weeks aged, 200-250 g b.w., were randomly divided into 4 groups, namely, K0 (normal rats), K1 (rats were given moderate-intensity aerobic exercise by animal treadmill 20 m/30 min), K2 (rats were given e-cigarette with 6 mg nicotine, 40% propylene glycol, and 60% vegetable glycerine 30 min for 5 days/week), and K3 (rats were given e-cigarette and moderate-intensity aerobic exercise). After exposure for 6 weeks, all animals were sacrificed to isolate the aorta for histopathological analysis with hematoxylin-eosin stain to evaluate the elastic fiber layer and intimal-medial thickness. The Verhoeff-Van Gieson staining was done for quantification elastic lamina fragmentation. Our study found that the e-cigarette group had the highest elastic lamina fragmentation among groups (8.14±2.85). The exercise only group showed the lowest elastic lamina fragmentation (2.50±1.87). Fragmentation in the e-cigarette and exercise group was higher than in the exercise only group (5.83±0.753 vs. 2.50±1.87, p=0.002). There is a significant difference of NO serum between four groups. The result of post hoc analysis using LSD showed that there is a significant difference of NO serum between K0 and K2, K0 and K3, K1 and K2, and K1 and K3. Therefore, our research demonstrated that the most injury of aorta elastic lamina was in the group that was exposed to e-cigarette that leads to vascular aging while exercise is not yet proven to reverse this effect.